Metabolic syndrome: concept and practical application - Lizarzaburu Robles, Juan Carlos (2013)
The metabolic syndrome (MS) is a cluster of metabolic abnormalities considered risk factors for developing cardiovascular disease and diabetes. MS components are defined according to different guidelines and consensus. The definition proposed by the National Cholesterol Education Program Adult Treatment Panel III (ATPIII) and the International Diabetes Federation (IDF) are the most commonly used in the different publications. These definitions have been updated in some populations according to ethnicity and geographical location, such as the Latin American Diabetes Association (ALAD) that defines a specific abdominal perimeter for Latin-Americans. In 2009 the publication Harmonizing the Metabolic Syndrome suggested a consensus on the application of unified diagnostic criteria for MS. Regarding the pathophysiology of MS, insulin resistance has been considered the main factor for development of the abnormalities associated with this syndrome; the abdominal or central obesity would be responsible for the development of insulin resistance. Adipokines produced in the abdominal fat would play a direct or indirect role in the development of MS components. It is important to consider the metabolic syndrome as equivalent to prediabetes because is also predicts diabetes. The rise in MS prevalence worldwide has increased the importance of this syndrome in the prevention and control of cardiovascular disease risk and diabetes. In the present article we review important aspects of the metabolic syndrome.